(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
RETRACTION TO: (2024). [Interactive E-Modules for Enhancing Religious Education]. [Edukasi], [22], [39-56]. doi:[doi: 10.32729/edukasi.v22.i1.1739]. This article has been retracted by the Publisher based on the following reason: The Editor of Jurnal Edukasi has identified an ethical violation related to the practice of gift authorship in the publication of this article. It was found that one of the listed authors did not meet the criteria for authorship as they did not make a substantial contribution to the research, as defined by the guidelines from the Committee on Publication Ethics (COPE). Following further investigation, it was clarified that the inclusion of this author was made without sufficient justification, which violates the required ethical standards for authorship. One of the conditions for submitting a paper for publication in this journal is that all authors must have made significant intellectual contributions to the work. The inclusion of an author who does not meet these criteria has resulted in the retraction of the article.